Oronasal Fistula and Complete Edentulism: What to Do? - Pushappreet Kaur; Jaspinder Kaur (MDPI AG, 2014)
Oronasal fistula is an internal fistula which represents an abnormal epitheliazed tract between oral and nasal cavity, thus impairing associated functions of deglutition and speech by nasal regurgitation of fluid and nasal speech respectively, besides risk of nasal infection resulting from food lodgement. This paper provides a brief yet definitive insight on the etiology, diagnosis and surgical closure of oronasal fistula along with a case report and discussion on prosthodontic rehabilitation of a 65 year old female with an iatrogenic oronasal fistula developed as a result of maxillary molar extraction using a complete metal based denture.